Validation of self-reported questionnaire to screen periodontal disease among diabetes patients: a study at 3 selected health centres in Kuantan - Tin, Myo Han; Ismail, Razida; Yaacob, Munirah; Md Aris, Mohd Aznan; Osman, Iskandar Firzada; Thuraiapprah, Mahendran; Sidek, Sorayah; Abdullah, Fa’iza; Than, Tun Sein; Saub, Roslan (2016)
there is growing evidence on bilateral relationship between diabetes mellitus (DM) and periodontal disease (PD)that PD affects glycaemic control. However, PD screening among DM-patients at diabetes-clinics is still limited. Self-reported questionnaire (SRQ) was developed to be used as a screen tool by non-oral health-practitioners, thus,SRQ can be used at diabetes-clinics to screen PD among DM-patients. Basic Periodontal Examination (BPE) is performed at dental clinics as a professional screening.